MEMAHAMI ALIRAN-ALIRAN TEOLOGI DALAM ISLAM (Polemik Sekitar Masalah Hubungan Akal-Wahyu Dan Perbuatan Manusia-keadilan Tuhan) - Mukhtar Nuhung (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The relationship of reason and revelation and man's deeds in relation to God's justice is a central theme polemical by theologians and scholars of Mutakallimin for years. This polemic, although generally still describes the advancement of thought in the Islamic world that, however, could divert the attention of Muslims from the themes that are actually more important and important to talk about. The relationship of reason-revelation, the Mu'tazila is the one that gives the most portion to reason and on the contrary, the Ash'ariyah more defends the authority of revelation than reason. As for al-Maturidi, they are more positioned on the central axis between the two streams, though revelation to them but is considered a fundamental reference. While the relationship of human deeds and justice of God, Jabariyah displays the fatalist thinking that is absolute that deny the involvement of human beings in creating his actions. On the contrary, the Mu'tazila greatly defends the human authority as the creator as well as the person in charge of his own deeds. Asy'ariyah and al-Maturidi, they tried to open the middle way as a solution to the polemic solution, but it still has not escaped from the fatalist Jabariyah thinking.